Perancangan Interior Pusat Terapi dan Sekolah Anak Autis di Surabaya - Jessica Celia; Adi Santosa (Intra, 2014)
Therapy Centre for Autism in Surabaya is a privately owned institution that engages in special education for children with special needs. The increasing number of children with autism is not matched by the number of school and therapy center for children with autism. In terms of the physical building, capacity, activity and space needs are still not sufficient. The design is intended to allow children with autism can grow to be better with the facilities provided such space one on one therapy, speech therapy room, space occupation, space sensory stimulation, gymnastic space, counseling rooms, a library, a ballroom, a health room, and space other support such as lobbies, offices, restrooms and service